Krieg und Frieden (1982) & Der Kandidat (1980) - Kluge, Alexander; Schlöndorff, Volker; Aust, Stefan; Engstfeld, Axel; Böll, Heinrich; von Eschwege, Alexander (München : Edition Filmmuseum, 2008)
Krieg und Frieden (War and peace): Documentary and film collage examining the short-range missile crisis at the peak of the Cold War, when neutron bombs could have potentially annihilated Central Europe. Includes fictive episodes at the end promoting an anti-nuclear, pro-peace message ("Space Talk," "Atom Bunker," and "Kill Your Sister"). Documentary footage of Chancellors Helmut Kohl and Helmut Schmidt in action, along with various European and American leaders highlight the urgent issues of the day. ##Der Kandidat (The Candidate): This political documentary puts together clips from newsreels, archives, and television to review the controversial career of Franz Josef Strauss who was running for Chancellor of West Germany at the time this documentary was made. Strauss founded the Christian Socialist Union and had a long political history as a parliamentarian (1949), Special Minister (1952), and by 1955 was Minister of Defense. His career began to unravel when a series of scandals hit the presses that involved him in kickbacks and abuses of power. Strauss was forced to resign his post as Defense Minister in the early 1960s. ##Krieg und Frienden = War and peace / directors, Stefan Aust, Alexander Kluge, Volker Schlöndorff (118 min., 1982) -- Auf der Suche nach einer praktisch-realistischen Haltung (12 min., 1983) -- Der Kandidat = The Candidate / directors, Stefan Aust, Alexander Kluge, Alexander von Eschwege, Volker Schlöndorff (124 min, 1980) -- Große Reiche muß man leiten wie man kleine Fischlein brät (15 min., 1993).
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander